Minimally invasive mesohepatectomy for centrally located liver lesions: a case series - Birgin, Emrullah; Hartwig, Vanessa; Rasbach, Erik; Seyfried, Steffen; Rahbari, Mohammad; Reeg, Alina; Jentschura, Sina-Louisa; Téoule, Patrick; Reißfelder, Christoph; Rahbari, Nuh Nabi (Surgical endoscopy and other interventional techniques, 2022)
Background: Resection of centrally located liver lesions remains a technically demanding procedure. To date, there are limited data on the effectiveness and safety of minimally invasive mesohepatectomy for benign and malignant lesions. It was therefore the objective of this study to evaluate the perioperative outcomes of minimally invasive mesohepatectomy for liver tumors at a tertiary care hospital. Methods: Consecutive patients who underwent a minimally invasive anatomic mesohepatectomy using a Glissonean pedicle approach from April 2018 to November 2021 were identified from a prospective database. Demographics, operative details, and postoperative outcomes were analyzed using descriptive statistics for continuous and categorical variables. Results: A total of ten patients were included, of whom five patients had hepatocellular carcinoma, one patient had cholangiocarcinoma, three patients had colorectal liver metastases, and one patient had a hydatid cyst. Two and eight patients underwent robotic-assisted and laparoscopic resections, respectively. The median operative time was 393 min (interquartile range (IQR) 298–573 min). Conversion to laparotomy was required in one case. The median lesion size was 60 mm and all cases had negative resection margins on final histopathological analysis. The median total blood loss was 550 ml (IQR 413–850 ml). One patient had a grade III complication. The median length of stay was 7 days (IQR 5–12 days). Time-to-functional recovery was achieved after a median of 2 days (IQR 1–4 days). There were no readmissions within 90 days after surgery. Conclusion: Minimally invasive mesohepatectomy is a feasible and safe approach in selected patients with benign and malignant liver lesions.
Gesehen am 22.05.2023